2020
DOI: 10.1186/s40663-020-00223-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of estimators of variance for forest inventories with systematic sampling - results from artificial populations

Abstract: Background: Large area forest inventories often use regular grids (with a single random start) of sample locations to ensure a uniform sampling intensity across the space of the surveyed populations. A design-unbiased estimator of variance does not exist for this design. Oftentimes, a quasi-default estimator applicable to simple random sampling (SRS) is used, even if it carries with it the likely risk of overestimating the variance by a practically important margin. To better exploit the precision of systemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 70 publications
1
18
0
1
Order By: Relevance
“…NFIs are typically based on approximate systematic grids of sample plots which generally produce conservative (i.e., too large) estimates of uncertainty if design-based estimators assuming simple random sampling (SRS) are used. Magnussen et al (2020) document the 100-year long quest of improving variance estimation in systematic sampling using model-based methods and add previously untested estimators to the set of alternatives to using simple expansion estimators with SRS. Of importance for NFIs, they conclude "In large populations, and a low sampling intensity, the performance of the investigated estimators becomes more similar" (Magnussen et al 2020).…”
Section: New Estimators and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…NFIs are typically based on approximate systematic grids of sample plots which generally produce conservative (i.e., too large) estimates of uncertainty if design-based estimators assuming simple random sampling (SRS) are used. Magnussen et al (2020) document the 100-year long quest of improving variance estimation in systematic sampling using model-based methods and add previously untested estimators to the set of alternatives to using simple expansion estimators with SRS. Of importance for NFIs, they conclude "In large populations, and a low sampling intensity, the performance of the investigated estimators becomes more similar" (Magnussen et al 2020).…”
Section: New Estimators and Methodsmentioning
confidence: 99%
“…In the context of the Finnish NFI, Räty et al (2020) found, however, that LPM-sampling could not markedly improve estimates based on systematic sampling when considering several variables of interest as is typical in NFIs. Complementing the study by Magnussen et al (2020), Räty et al (2020) identify a variance estimator originally developed for LPM that is well-suited for systematic sampling.…”
Section: New Estimators and Methodsmentioning
confidence: 99%
“…Langsaeter 1932Langsaeter , 1934. Among these was a work on uncertainty estimation in systematic strip sampling (Langsaeter 1926) which contained early descriptions of estimators that are still studied today (Magnussen et al 2020).…”
Section: Research and The Role Of International Cooperationmentioning
confidence: 99%
“…The NFI web interface is available in English and Norwegian and gives access to standard NFI data as well (Breidenbach 2016(Breidenbach -2020. Although alternative options are currently considered (Magnussen et al 2020), conservative variance estimators assuming simple random sampling are utilized in the NFI web interface.…”
Section: Utilization Of Remotely Sensed Datamentioning
confidence: 99%
“…[25][26]. However, many studies have demonstrated that such estimators may significantly overestimate the true variance [5,6]. Biased estimators of sampling variance can result in a misallocation of resources, as a larger sample size than is necessary to meet some minimum desired precision may be suggested using an inflated variance estimator.…”
Section: Introductionmentioning
confidence: 99%